Duplex γ/α-phase evolution of biocompatible high-nitrogen stainless steel in additive manufacturing - Yufeng Tao; Liansheng Lin; Xudong Ren; Xuejiao Wang; Xia Cao; Yunxia Ye; Erjin Zhang; Heng Gu; Zijie Dai (Journal of Materials Research and Technology)
Addressing the escalating complexity and performance demands of stainless steels in industrial and biomedical contexts, duplex-phase high-nitrogen (N) nickel-free stainless steel (DHNAS) comprising austenitic (γ) and ferritic (α) phases represents a prospective solution. By synergistically integrating γ-phase ductility and α-phase strength via dislocation density engineering, DHNAS demonstrates exceptional adaptability for mass production or bespoke applications. However, opaque process-property relationships, microstructural inhomogeneity, and geometric constraints hinder its additive manufacturing (AM) capabilities. This work incorporates laser selective melting protocols with gas-atomized BiossN micro-powders to unravel the thermodynamic evolution of γ/α duplex-phase during the AM process. Through parameter modulation, we establish predictive phase fraction control (0.5–44.9 % γ-phase), achieve high nitrogen supersaturation (1.01 wt% via Mn alloying and N2 gas protection), and maintain exceptional biocompatibility (>99 % fibroblast viability over 14-day cytotoxicity assays). Artificial tunability of microstructured high-nitrogen γ/α duplex-phase at tight topological control promises transformative opportunities not possessed by individual ferrite or austenitic phase, allowing pre-programming mechanics (density, strength, hardness, and tensile properties) for next-generation industrial or implantable biomedical uses requiring complex geometries and multi-functions.